Litterfall and nutrient return in different plant communities of Northeastern Mexico - López Hernández, Juan M.; González-Rodríguez, Humberto; Cantú-Silva, Israel; Gómez-Meza, Marco V.; Estrada-Castillón, Andrés E.; Contreras-Guajardo, Norma L.; del Valle-Arango, Jorge I. (Ecosistemas y Recursos Agropecuarios, 2022)
The litterfall that accumulates in the forest soil and its further decomposition play an important roll in the maintenance of productivity in different terrestrial ecosystems since its constitute the main flow of nutrients to the soil. The objective of this study was to evaluate the production of litterfall, its nutrient return thru litterfall deposition and macro-nutrient use efficiency. The study was conducted in Linares, Crucitas and Los Ramones, state of Nuevo León, México. Average litterfall deposition was 5 800, 5 270 and 6 596 kg ha−1 year−1 for Linares, Crucitas and Los Ramones, respectively. Total nutrient return thru litterfall followed the sequence: Linares > Crucitas > Los Ramones, with value of 135, 122 and 101 kg ha−1 year−1, respectively. Even though the return of P thru litterfall was the lowest, P nutrient use efficiency was higher with respect to Ca, Mg and K. Greatest nutrient use efficiency in terms of Ca and Mg was observed in Los Ramones, K in Crucitas and P in Linares. The results showed that there exist spatial and temporal variation in the production of litterfall, nutrient return and nutrient use efficiency between studied sites. Thus, litterfall deposition, nutrient return and nutrient use efficiency between sites depend on stand composition and richness, edaphic properties, litterfall quality, and plant phenology.